GAMBARAN KELELAHAN KERJA SUBJEKTIF PADA OPERATOR MESIN PRODUKSI PAKAN IKAN - Tria Melissa; Endang Dwiyanti (The Indonesian Journal of Occupational Safety and Health, 2018)
Fatigue is a subjective feeling that everyone feels. Work fatigue may occur due to various factors such as age, years of working life, nutritional status, and noise. The purpose of this study was to know the relation between the factors cause work fatigue at fish feed production machine operator. This research was descriptive observational with cross-sectional design. Population in this research is all worker machine operator of fish feed production who worked in the same shift at the time of the research. Samples were taken with a total sampling principle that all operator’s workers from production area who totaled 24 people. The variables were age, years of working life, nutritional status, noise, and subjective work fatigue. The results showed that most of the respondents were over 40 years old, had a working period over 10 years, had normal nutritional status, worked in the work area exceeding the noise treshold limit value and had moderate fatigue. The conclusions of this study are age, years of working life, and nutritional status has no relationship causing fatigue. Noise can be one of the factor of the occurrence of work fatigue because (54.2%) workers who work in the work area exceeding the standardize had a moderate fatigue.Keywords: noise, nutritional status, worker, work fatigue